The Effect of Computerized Cognitive Behavioral Therapy on People's Anxiety and Depression During the 6 Months of Wuhan's Lockdown of COVID-19 Epidemic: A Pilot Study - Lv, Zhangwei; Li, Jinyang; Zhang, Bin; Zhang, Ning; Wang, Chun (Frontiers in Psychology, 2021)
Background: The effectiveness of computerized cognitive behavioral therapy (CCBT) has been proven for mild and moderate anxiety and depression. In 2016, the first official Chinese CCBT system was launched by Chinese Cognitive Behavior Therapy Professional Organizations and included four items: getting out of depression, overcoming anxiety, staying away from insomnia and facing Obsessive-compulsive disorder. This study explored the effects of CCBT on anxiety and depression by comparing the use of the platform during the epidemic and during the same period in 2019. Methods: Users were divided into a depression group or an anxiety group according to their own discretion. The subjects used the self-rating anxiety scale (SAS) and self-rating depression scale (SDS) before each training. This study compared the demographic characteristics, depression and anxiety levels of CCBT platform users during the lockdown period in Wuhan (LP2020) from January 23 to July 23, 2020 and the same period in 2019 (SP2019). Result: (1) There were significant differences in gender (χ2 = 7. 215, P = 0. 007), region (χ2 = 4. 225, P = 0. 040) and course of disease (χ2 = 7. 867, P = 0. 049) between the two periods. (2) There was a positive Pearson correlation between the number of users of CCBT platform during LP2020 and number of confirmed cases of COVID-19 in each province (r = 0. 9429, P < 0. 001). (3) In LP2020, the SAS (t = 2. 579, P = 0. 011) and SDS (t = 2. 894, P = 0. 004) scores at T0 in Hubei were significantly higher than those in other regions. (4) The CCBT platform has an obvious effect on anxiety (F = 4. 74, P = 0. 009) and depression on users (F = 4. 44, P = 0. 009). Conclusion: This study showed women, students and people who are more seriously affected by the epidemic were more likely to accept the CCBT training. The CCBT platform made a significant contribution towards alleviating the anxiety and depression symptoms of users during the epidemic. When face-to-face psychotherapy is not available , CCBT can be used as an effective alternative.